The impact of marketing mix on the decision-making process to purchase PT MGD transportation services in Indonesia - Felim, William; Sitinjak, Tony (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
This study aims to investigate the effect of marketing mix on the decision process to purchase transportation services at PT. MGD. This study uses product, price, place, and promotion as independent variables and the decision process variable to purchase PT. MGD's transportation services as the dependent variable. The authors expect that independent variables significantly influence the dependent variable. By using α of 5 percent, the study found that product and place significantly impacted the purchasing decision process of PT. MGD's transportation services. While α increased to 10%, all independent variables significantly impacted the dependent variable. Further research can utilize additional variables because the independent variables used in this study can only explain 53.10% of the purchasing decision process. Other variables explain 46.9 % of it.